PENGARUH PRESTASI KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT TELKOM AKSES) - Elisy, Cindy Putry; Pranoto, Suryo Budi (LPPM Universitas Putera Batam, 2020)
In a company, human resources are one of the elements that play an important role. Therefore in the world of business that is growing increasingly rapidly now and the development of increasingly sophisticated knowledge and technology, it will bring changes in the life patterns of employees so that they can work optimally as human resources in it. The formulation of the problem in this study explains how the effect of work performance partially on employee performance, the effect of partial incentives on employee performance and how the influence of kejra achievement and incentives together - on the performance of The population in this study were employees of PT Telkom Akses, specifically the Batam area. The sampling technique is the census technique (Sensus Sampling) with 113 respondents in the research method using multiple linear regression analysis. The results of the study and the hypothesis indicate that Work Performance and Incentives partially and simultaneously have a significant effect on Employee Performance.